La Economía y la Reinvención del Estado Mexicano - Vargas, José (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
For the last few years, the importance of the role of the state in formulating and implementing economic policies to achieve growth and development of society, broadly speaking, both state and society have undergone a lot of changes and transformations. In Mexico, the so called neoliberal model of state has been impossed over a former protectionist, statist and populist regimes and had achieved some impressive results in terms of economic growth and development, although this rate "falls well below the 3.4 percent GDP growth" that the World Bank considers neccesary to reduce poverty. Regarding this last issue, the largest increase has resulted of implementing the structural adjustment policies and the new social policies (Programa Nacional de Solidaridad). The results are dissapointing with the increasing of unmeployment rate, the slumping of incomes, the widening of the gap betwen the rich and the poor and thus, fissures in the Mexican society while fueling guerrilla’s warfare and crime waves. In fact, at the turn of the new millennium, the debate on the model of state that not only a more globalizad and highly developed societies, but also the less developed societies, such as the case of Mexico, require, is takeing more importance. The mains issues of this discussion focus on fundamental concepts of representation, economic functions and organization of the Mexican state.